2021
DOI: 10.1016/j.xkme.2021.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Testing for Chronic Kidney Diseases: Clinical Utility and Barriers Perceived by Nephrologists

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…Increased funding was widely called for, by several individuals, as critical to support and facilitate the genomic testing and services provided. This is consistent with a previous study surveying nephrologists in the United States that also demonstrated cost was one of the most important barriers, as well as a lack of ease of use and poor availability of tests [ 18 ]. In addition to funding for testing, nephrologists reported a lack of overall resources to support and sustain the presence of genetics services across Australia.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Increased funding was widely called for, by several individuals, as critical to support and facilitate the genomic testing and services provided. This is consistent with a previous study surveying nephrologists in the United States that also demonstrated cost was one of the most important barriers, as well as a lack of ease of use and poor availability of tests [ 18 ]. In addition to funding for testing, nephrologists reported a lack of overall resources to support and sustain the presence of genetics services across Australia.…”
Section: Discussionsupporting
confidence: 92%
“…Within nephrology, previous research assessed nephrologists’ attitudes and practices, as well as perceived barriers and interventions to the uptake of genomic medicine through a mixed methods electronic survey [ 16 ]. The findings demonstrated low uptake and confidence in genomic medicine by nephrology specialists, consistent with findings from studies of other specialists and primary care providers [ 17 , 18 , 19 ]. Most believed genomics to be useful in clinical care [ 2 , 16 ].…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…The use of a broad panel for genetic diagnosis for kidney diseases has multiple advantages for clinicians, minimizing the need to identify the correct genetic panel or prioritize panels for individuals with an overlap of symptoms. Use of a single test for a wide range of patients allows physicians to become familiar with a single process for ordering, insurance ascertainment, cost, and results reporting, which have previously been identified as obstacles for use of genetic testing among nephrologists [4, 34]. In addition, unexpected findings for rare diseases that were not under consideration will improve diagnostic accuracy.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“… 10 The expertise in renal genetic clinics could be a valuable resource, as barriers for nephrologists to adopt genetic tests have been noted. 11 …”
mentioning
confidence: 99%